Potential and Barriers to Development in Atule'er Village - Styawati, Endah; Kristy, Abelia (Confucius Institute Universitas Sebelas Maret, 2023)
Tourist villages, in general, are rural areas with several characteristics worthy of being used as tourist destinations. It has several supporting factors, such as a unique location, unique accessibility to the village and a socio-economic system that also colours the tourist village. The village with steep stairs leading to the sky in the Daliang Mountains, Atule'er Village, Sichuan Province, China, is known as